ENSINO DE REPERTÓRIOS POR MEIO DE FEEDBACK INSTRUCIONAL EM CRIANÇAS COM TRANSTORNO DO ESPECTRO AUTISTA (TEA) - CORDEIRO, Neylla Cristhina Pereira (2020)
Applied Behavior Analysis (ABA) is concerned with teaching verbal and non-verbal repertoires in children with ASD. Some repertoires involve category discrimination. There are cases of category tact (for example, saying "means of transport" in front of a car); identification of categories as listener (for example, selecting a car picture in front of the instruction "show means of transport"); arbitrary visual-visual pairings (for example, matching the image of a car to that of a motorcycle); intra-verbal categories (for example, saying “car, motorcycle and truck” in front of “tell me names of means of transport”). One procedure that can produce these repertoires is called instructional feedback. This includes the inclusion of secondary targets when teaching primary targets. For example, a teacher teaches a child to emit the simple “car” feel in the face of a car (primary target). Additional information, "it is a means of transport", is then presented by the teacher. Probes reveal that a child starts to say “it is a means of transportation” under the control of the car figure (secondary target). The objective of the research was to evaluate whether the teaching of simple tacts with instructional feedback would produce emergence of repertoires to categorize without direct teaching in four children with ASD. Ages range from 5 to 7 years. There were figures used depicting states in the Southeast and Northeast regions of Brazil, and figures from the regions, as well as figures from times of football and their states. As a result, categorizing repertoires emerged for three children (with variability for one of them). In the case of the child in which an emergency effect was not characterized, the teaching of categories was implemented and, thus, the other repertoires emerged. The data replicate and extend what has been produced by the previous literature, reflecting the potential of instructional feedback in increasing the efficiency of teaching, due to the establishment of repertoires beyond what is directly trained. The data were also discussed based on a possible relationship between teaching and the bidirectional naming theory proposed at ABA.